2020 IEEE 23rd International Conference on Intelligent Transportation Systems (ITSC) 2020
DOI: 10.1109/itsc45102.2020.9294751
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle Automation Field Test: Impact on Driver Behavior and Trust

Abstract: With the growing technological advances in autonomous driving, the transport industry and research community seek to determine the impact that autonomous vehicles (AV) will have on consumers, as well as identify the different factors that will influence their use. Most of the research performed so far relies on laboratory-controlled conditions using driving simulators, as they offer a safe environment for testing advanced driving assistance systems (ADAS). In this study we analyze the behavior of drivers that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Other studies that reported the take over reaction time (TOrt) in different scenarios showed that TOrt stayed fairly consistent, between 2 and 3.5 seconds [23]. However, experiments performed under real driving conditions showed that drivers needed less than one second to take back the control of the vehicle, this time varying depending on the road conditions and tasks performed [15].…”
Section: Related Workmentioning
confidence: 98%
See 3 more Smart Citations
“…Other studies that reported the take over reaction time (TOrt) in different scenarios showed that TOrt stayed fairly consistent, between 2 and 3.5 seconds [23]. However, experiments performed under real driving conditions showed that drivers needed less than one second to take back the control of the vehicle, this time varying depending on the road conditions and tasks performed [15].…”
Section: Related Workmentioning
confidence: 98%
“…This is the case, for example, in curvy roads driven at high speed [14]. Several studies have investigated driver reactions in this scenario, the work in [15] showing that the road features affect the driver's level of visual attention and trust in the automation. Additional research indicated that the existence of curves increased lateral acceleration and reaction time to respond to a TOR [16].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, during conditional automation, a timely response from a driver during a take-over request in the event of an unexpected situation is crucial to ensure road safety. To this end, the effect of nondriving tasks in a real-world environment is assessed, taking into account a driver's state and the environment [4], [5].…”
Section: Human Factors and Interaction With Intelligent Vehiclesmentioning
confidence: 99%